Struktur Polisentris Kota Makassar - Muh. Nur Fajri; Ihsan Ihsan; Isfa Sastrawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2015)
Cities that have several downtowns are called polycentric cities. Rapid development and growth in urban areas results in inefficiency in services by just one service center. Polycentric city structures occur in many large cities that have the characteristics of the decentralization of the function of activities outside the function of activities in the middle of the city. Makassar City is one of the metropolitan cities in Indonesia. Makassar City consists of 14 sub-districts that have diverse regional developments. The emergence of indications that Makassar City does not only have one city center is the background of this study. The purpose of this study is to describe the pattern of polycentric structure of Makassar City and what factors influence the polycentric structure of Makassar City. This research uses overlay mapping analysis, photo mapping, qualitative and quantitative approaches. Secondary data sources to describe the polycentric structure of Makassar City using yellow pages and categorized into 5 firms or activity functions. Yellow pages are used to obtain information in the form of an address or location of the type of activity that is located. Mapping analysis uses ArcGis software which includes ArcMap and ArcScene to show the contours or intensity of activities in several areas in Makassar City. The results of this study are in the form of the polycentric structure of Makassar City covering the Karebosi, Panakukkang, Bumi Tamalanrea Permai and Daya Settlements. Factors affecting polycentric structures among other things, city centers, tourism, industry and settlements.